2014
DOI: 10.1515/epoly-2014-0029
|View full text |Cite
|
Sign up to set email alerts
|

Competition in aluminium phosphinate-based halogen-free flame retardancy of poly(butylene terephthalate) and its glass-fibre composites

Abstract: Aluminium diethylphosphinate (AlPi-Et) and inorganic aluminium phosphinate with resorcinol-bis(di-2,6-xylyl phosphate) (AlPi-H+RXP) were compared with each other as commercially available halogen-free flame retardants in poly(butylene terephthalate) (PBT) as well as in glass-fibre-reinforced PBT (PBT/GF). Pyrolysis behaviour and flame retardancy performance are reported in detail. AlPi-H+RXP released phosphine at very low temperatures, which can become a problem during processing. AlPi-Et provided better limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 24 publications
5
48
0
Order By: Relevance
“…Decrease in EHC and increase of CO yield leveled off with increasing P‐content and indicated that the gas phase effectivity of DOPO decreased at higher concentrations. This kind of leveling off has been reported before for flame inhibition by several P‐containing flame retardants and is a typical effect of P‐containing species in the gas phase . DOPO polyesters with C:O ratios between 3.5:1 and 1.5:1 in the polymer backbone were investigated.…”
Section: Resultssupporting
confidence: 62%
“…Decrease in EHC and increase of CO yield leveled off with increasing P‐content and indicated that the gas phase effectivity of DOPO decreased at higher concentrations. This kind of leveling off has been reported before for flame inhibition by several P‐containing flame retardants and is a typical effect of P‐containing species in the gas phase . DOPO polyesters with C:O ratios between 3.5:1 and 1.5:1 in the polymer backbone were investigated.…”
Section: Resultssupporting
confidence: 62%
“…Gas-phase flame inhibition and condensed phase flame retardancy were coordinated in FR composites. Additionally, the compact char layer played the protective effect in FR composite [22]. In general, the flame inhibition and charring decreased PHRR and THE values, whereas the protective effect of the char decreased PHRR values.…”
Section: Flame Retardant Mechanisms Of Fr Pc/abs Compositementioning
confidence: 92%
“…The onset decomposition temperature (T 5% ) of PC/ABS was 394.3 C, and PC/ABS alloy presented two temperatures of maximum weight loss rate: the first T max of PC/ABS alloy was approximately 437.0 C, and the second T max was approximately 500.5 C. The FR PC/ABS composites presented three temperatures of maximum weight loss rate. The first T max of the PC/ ABS/AHP composites was approximately 345.2 C due to the decomposition of AHP [22,27]; T max2 and T max3 were approximately 431.5 C and 500.5 C, respectively, which corresponded to the decomposition of PC/ABS alloy. The T 5% value of PC/ABS/AHP and PC/ABS/AHP/EMA composites decreased to 345.3 C and 350.2 C, reduced approximately 50 C compared to that of PC/ABS alloy, which indicated that the addition of AHP had very obvious influence on the thermal stability of FR PC/ABS composite.…”
Section: Mechanical Properties Of Fr Pc/abs/ema Compositesmentioning
confidence: 97%
“…4,5 During its long lifetime or applications in extreme surroundings, such as construction, shipbuilding, or in nuclear, automotive, or photovoltaic applications, 6 several service conditions (mainly the weathering exposures) are inevitable, including UV irradiation, temperature, and humidity, and sometimes even salt spray. Aluminum hydroxide (ATH) [11][12][13][14][15][16] and phosphoruscontaining flame retardants, such as aluminum diethyl phosphinate (AlPi-Et), [17][18][19][20] aluminum hypophosphite, 21 aluminum phosphate, 22 and ammonium polyphosphate (APP) [23][24][25][26] have been proposed and utilized extensively, exhibiting good flame retardancy in EVAs. 6 Accordingly, it is important and necessary to investigate the long-term durability of cables exposed under different weathering conditions, as well as the deterioration of flame retardancy.…”
Section: Introductionmentioning
confidence: 99%